Prediction the photovoltaic system performance via artificial neural network (ANN) technique - Jumaat, Siti Amely; Mohamed, Abdou Mani; Mohamad Nor, Ahmad Fateh (2024)
Population growth and industrialization are driving up global energy consumption, which is expected to soar in the near future. However, the predominant use of fossil fuels exacerbates environmental pollution and greenhouse gas emissions, which are primary contributors to global warming. To address this, this study proposes an artificial neural network (ANN) model designed to forecast the power output of both monocrystalline and polycrystalline photovoltaic (PV) panels. The aim is to assess the performance and efficiency of these two PV panel types. Data spanning from 2018 to 2020 was gathered, with meteorological parameters serving as input for the ANN model. Polycrystalline panels exhibit higher voltage output, whereas monocrystalline panels typically yield greater current. The model's mean square error (MSE) for training, testing, and validation equated, indicating robust learning during training without overestimation. Both models demonstrate an excellent fit to the data, evident from the correlation coefficient (R) reaching 1. The predicted values closely align with actual trends for both panel types, with insignificant disparities in estimated voltage, current, and power. Overall, the polycrystalline panel outperforms the monocrystalline panel, boasting efficiencies of 0.999% and 0.997%, respectively